Cyclic Hydrostatic Pressure Promotes A Stable Cartilage Phenotype And Enhances The Functional Development Of Cartilaginous Grafts Engineered Using Multipotent Stromal Cells Isolated From Bone Marrow And Infrapatellar Fat Pad. - BUCKLEY, CONOR; KELLY, DANIEL (My University, 2014)
The objective of this study was to investigate how joint specific biomechanical loading influences the functional development and phenotypic stability of cartilage grafts engineered in vitro using stem/progenitor cells isolated from different source tissues. Porcine bone marrow derived multipotent stromal cells (BMSCs) and infrapatellar fat pad derived multipotent stromal cells (FPSCs) were seeded in agarose hydrogels and cultured in chondrogenic medium, while simultaneously subjected to 10 MPa of cyclic hydrostatic pressure (HP). To mimic the endochondral phenotype observed in vivo with cartilaginous tissues engineered using BMSCs, the culture media was additionally supplemented with hypertrophic factors, while the loss of phenotype observed in vivo with FPSCs was induced by withdrawing transforming growth factor (TGF)-?3 from the media. The application of HP was found to enhance the functional development of cartilaginous tissues engineered using both BMSCs and FPSCs. In addition, HP was found to suppress calcification of tissues engineered using BMSCs cultured in chondrogenic conditions and acted to maintain a chondrogenic phenotype in cartilaginous grafts engineered using FPSCs. The results of this study point to the importance of in vivo specific mechanical cues for determining the terminal phenotype of chondrogenically primed multipotent stromal cells. Furthermore, demonstrating that stem or progenitor cells will appropriately differentiate in response to such biophysical cues might also be considered as an additional functional assay for evaluating their therapeutic potential.
PUBLISHED
Keywords: Cartilage repair; Functional tissue engineering; Mesenchymal stem cell; Multipotent stromal cell; Next Generation Medical Devices